TRANSMISI BUDAYA DAN PERKEMBANGAN INSTITUSI PENDIDIKAN - Suwardi Suwardi (Ensiklopedia Education Review, 2019)
Education can be defined as a learning process, providing knowledge, skills and attitudes through thoughts, character and physical capacity by using institutions so that the goals to be achieved can be met. Education can be obtained through formal and informal institutions. Transmission of culture through informal institutions is carried out through enculturation since childhood in his family environment. In a highly complex, specialized and rapidly changing society, education has a very large function in understanding culture as a whole. With the acceleration of cultural change, the more time it takes to understand one's own culture. This makes the culture of the future unpredictable, so that learning a new culture requires a new method of learning it. In this case, educators and anthropologists must work together, where both of them have an important and interconnected role. Keywords: Transmission, Culture, Development, Educational Institutions.